The Correlation Between Digital Literacy and Collaboration Skill with Environmental Literacy of Class X Students of SMAN 2 Malang - Nurjannah Nurjannah; Mimien Henie Irawati Al Muhdhar; Agus Dharmawan; Ruchimah Achmad; Laily Asfany (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Digital literacy (X1) and collaboration skills (X2) related to environmental literacy (Y) are the superior characteristics to use digital and to work together in solving various environmental issues. This study aims to determine the relationship between X1 and X2 with Y class X students at SMAN 2 Malang. The research uses a quantitative approach with descriptive research types and linear regression tests. The sample used was class X LMT-1 Biology with 33 students consisting of students majoring in Social Sciences and Languages. The instruments used were the X1 questionnaire, the X2 questionnaire, and the Y questionnaire. The results of the study showed that then correlation coefficient values X1Y, X2Y, X1X2, X1X2Y respectively 0.125: 0.401; 0.593; 1.119. From the overall results of the data analysis, it was found that digital literacy and environmental literacy have a very weak correlation. Collaboration skills and environmental literacy are sufficiently correlated. Digital literacy and collaboration skills have a strong correlation. Digital literacy and collaboration skills provide a perfect or very strong correlation to environmental literacy.